Local exchange through community currency in an alternative gift economy : an anthropological analysis of the Cape Town talent exchange - Coetzee, Liezl (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2010.